Xizang Yaluzangbujiang zhong you di qu tu di xi tong - Liu, Yanhua (Beijing : Ke xue chu ban she : Xin hua shu dian Beijing fa xing suo fa xing, 1992)
Soil system in the region of the middle stream of Brahmaputra River, Tibet, China.
Includes bibliographical references.
Keywords: Soils -- Brahmaputra River Region